Esther en alguna parte - Eimil, Eduardo; Miravalles, Reinaldo; Molina, Enrique, 1943-2021; Granados, Daisy; Alberto, Eliseo, 1951-2011 (ICAIC ; Sontrac E.I.R.L., 2013)
A year after the death of his wife Maruja, Lino Catalá, a serious and formal old man, is approached by Larry Pó, a quirky old man with multiple personalities, who tells him that his wife was leading a double life: by day a housewife common and current, and at night an imposing singer of boleros. From this moment, the two elders join in a thorough search in the past of Maruja, while trying to find the whereabouts of Esther Rodenas, the great love of Larry's life. While they follow the trail of the two women they loved, there arises between them a friendship that transforms them in a definitive way.